Cellulose microcrystal improved interphase of ramie fiber‐reinforced epoxy resin composites. (30th August 2017) - Zhang, Kaomin; Zhao, Yan; Dong, Xiang; Li, Ruyan
Abstract : This article investigated the effect of cellulose microcrystal (CMC) and low molecular polyamide (PA650) on the mechanical and water absorption properties of ramie fiber‐reinforced epoxy composites. Results showed that coating mixture of CMC and PA650 (CMC/PA650) on the surface of ramie fiber improved the interfacial adhesion strength of ramie fiber/epoxy composites. As a result, the flexural strength, flexural modulus, and interlaminar shear strength of PA650/CMC‐coated ramie fabric‐reinforced epoxy composites (CPRFC) were 10.6%, 8.1%, and 7.4% higher than those of ramie fabric without coating reinforced epoxy composites (RFC). Additionally, saturated water absorption of CPRFC was reduced by 40.5% and 31.5% than that of RFC and PRFC, it seems that a water‐resistant interphase exists in the CPRFC and it is more efficient at the early stage of water immersion. However, without filling of CMC in PA650, lowest flexural modulus and highest flexural strain of the composites were found. POLYM. COMPOS., 39:E2207–E2216, 2018. © 2017 Society of Plastics Engineers